2021
DOI: 10.3390/toxics9120349
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Effects of Enrofloxacin on Carbendazim-Induced Developmental Toxicity in Zebrafish Embryos

Abstract: Carbendazim (CAR) and enrofloxacin (ENF) are frequently detected in fruits and meat products, respectively. Since most people consume fruits, vegetables, and meat products, combined exposure is possible, necessitating further evaluation of toxic interactions. In this study, the developmental toxicity of separate and combined exposure was examined in zebrafish embryos. Carbendazim exposure at 0.79 mg/L and above significantly affected developmental parameters, while enrofloxacin alone had no substantial effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…For example, Luan et al (2022) suggested that enrofloxacin-ciprofloxacin and enrofloxacin-florfenicol pairs exhibited synergistic cytotoxicity at specific concentrations in human hepatocytes, while enrofloxacin and sulfadimidine induced synergistic cytotoxicity at all tested concentrations [136]. Fan et al (2022) found that enrofloxacin and carbendazim coexposure reduced the hatching rate at 48 h postfertilization and increased the hatching malformation and lethality rates at 96 h postfertilization in zebrafish embryos, which indicated that the antagonistic toxicity effects might be related to the reciprocal effects of metabolism-related genes, such as cyp7a1 and apoa1a [137]. Zhao et al (2018) found that ciprofloxacin and zinc oxide (ZnO) nanoparticle complexes induced additive toxic effects on methanogenesis and the degradation of proteins and carbohydrates.…”
Section: Toxicity Evaluation Of Mixing Residual Fq Antibiotics and Ot...mentioning
confidence: 99%
“…For example, Luan et al (2022) suggested that enrofloxacin-ciprofloxacin and enrofloxacin-florfenicol pairs exhibited synergistic cytotoxicity at specific concentrations in human hepatocytes, while enrofloxacin and sulfadimidine induced synergistic cytotoxicity at all tested concentrations [136]. Fan et al (2022) found that enrofloxacin and carbendazim coexposure reduced the hatching rate at 48 h postfertilization and increased the hatching malformation and lethality rates at 96 h postfertilization in zebrafish embryos, which indicated that the antagonistic toxicity effects might be related to the reciprocal effects of metabolism-related genes, such as cyp7a1 and apoa1a [137]. Zhao et al (2018) found that ciprofloxacin and zinc oxide (ZnO) nanoparticle complexes induced additive toxic effects on methanogenesis and the degradation of proteins and carbohydrates.…”
Section: Toxicity Evaluation Of Mixing Residual Fq Antibiotics and Ot...mentioning
confidence: 99%
“…The mixed ratio signi cantly affected synergistic toxicity. For example,Luan et al (2022) suggested that enro oxacin-cipro oxacin and enro oxacin-orfenicol pairs exhibited synergistic cytotoxicity at speci c concentrations in human hepatocytes, while enro oxacin and sulfadimidine induced synergistic cytotoxicity at all tested concentrations Fan et al (2022). found that enro oxacin and carbendazim coexposure reduced the hatching rate at 48 hours postfertilization and increased the hatching malformation and lethality rates at 96 hours postfertilization in zebra sh embryos.…”
mentioning
confidence: 99%